An Analysis of Students’ Skill in Writing Announcement Text at SMA Ekasakti Padang - Yesi Handriani; Yessy Marzona; Lailatul Husna (Kilau Publishing, 2026)
This study aims to analyze students’ skills in writing announcement texts at SMA Ekasakti Padang. This research employed a descriptive quantitative method. The population of the study consisted of tenth-grade students of SMA Ekasakti Padang, and the sample was selected through random sampling. The instrument used was a writing test requiring students to compose an announcement text. The data were analyzed using a scoring rubric covering content, organization, vocabulary, grammar, and mechanics. The results show that students’ overall writing skill was at a moderate level. Students performed relatively well in content and organization, but they experienced difficulties in grammar and vocabulary. These findings indicate the need for more intensive writing practice and teacher feedback to improve students’ writing skills in announcement texts.